Uji Uses and Gratifications dalam Intensitas Menonton Program Talk Show Melalui Televisi - Rizca Haqqu (CoverAge: Journal of Strategic Communication, 2020)
A survey of media consumption in several cities throughout Indonesia shows that television use still dominates. The results of a survey conducted by the Indonesian Broadcasting Commission explained that television programs considered to have quality with a high standard value of 3.04 were talk show programs. The purpose of this study is to examine the use of media and its underlying relationships based on the standpoint of the uses and gratification theory. This research uses theories of uses and gratification. The theory of uses and gratification considers that mass media do not have the power to influence the audience, but the audience using mass media is certainly based on different needs. An explanatory quantitative approach is used in this study to explain a social phenomenon that can be measured. Correlation test results in this study explained that the entertainment satisfaction obtained by respondents did not come from the intensity of the respondents when watching talk show s through television media, but the high level of entertainment satisfaction obtained by respondents came from the magnitude of the desired information motive.